Examining the Temporal Structure of the Perception–Production Link in Second Language Acquisition: A Longitudinal Study. Issue 1 (6th December 2017) - Nagle, Charles L.
Abstract: Most studies on the perception–production link have assumed a synchronous relationship according to which gains in perception transfer to production rapidly and efficiently. However, time‐lagged and asymptotic relationships are also possible, where perception would guide production at a later stage or production would improve only once perception has reached a high level of accuracy. This study investigated the temporal dynamics of the perception–production link by modeling English speakers' ability to perceive and produce second language (L2) Spanish stops over time. Mixed‐effects modeling of the d′ perception and voice onset time (VOT) production data demonstrated significant development in both areas. Time‐lagged change models indicated a change in d′ significantly related to decreasing VOT in L2 /p/ at the following testing time, but no significant relationships emerged between perception and production of L2 /b/. Multiple patterns among individuals emerged. Results are interpreted in light of contemporary models of L2 speech learning. Open Practices: This article has been awarded an Open Materials badge. Study materials are publicly accessible in the IRIS digital repository athttp://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .